(untitled) - Convention on International Trade in Endangered Species (CITES) (Switzerland, 2008)
The goal of the CITES college e-seminar series 2008 is to make available capacity building tools based on new information and comunication technologies to conserve biodiversity and contribute to its sustainable use.
Keywords: Biodiversity,Sustainable development,Đa dạng sinh học,Phát triển bền vững